Analysis of Kaiso as A Transcription Factor - Baig, Akeel (My University, 2002)
Recently, through reporter gene studies, the novel BTB/POZ protein, Kaiso, has been identified as a transcriptional repressor. The purpose of this study was to determine if Kaiso recruited the Histone Deacetylase Complex to mediate repression and if the previously identified Kaiso Binding Site (KBS; TCCTGCNA) is a physiological target regulated by Kaiso. The two objectives are complementary because an HDAC interaction identifies the mechanism of transcriptional regulation used by Kaiso and regulation of the KBS element identifies a novel, non-methylation dependent, physiological target under transcriptional regulation by Kaiso. Through coimmunoprecipitation and Western blot analyses, Kaiso does not interact with HDAC1, HDAC2 or mSIN3A. These results were surprising since all three of these proteins are common to a variety of repression complexes. mSIN3A is a common component of SIN3 mediated repression and HDAC1/HDAC2 are part of various repression complexes including SIN3, NuRD and CtBP. Although the remaining HDAC proteins were not assayed for an interaction, Kaiso transcriptional activity was demonstrated to be insensitive to the HDAC inhibiting drug, Trichostatin A (TSA). These results indicate either a non-HDAC mechanism of action or alternatively, transcriptional activation. Complementary to the observations of no Kaiso-HDAC interaction and TSA insensitivity was the findings that Kaiso activates transcription of the KBS cis-element in HCT116, HCA-7 and 293 cells, but not MOCK cells in reporter gene assays. Taken together, these results indicate that Kaiso is a dual functioning protein capable of both transcriptional activation and repression and that the mechanism of repression is not through the direct recruitment of HDAC proteins.
Keywords: transcriptional repressor, physiological target, Kaiso, mechanism